Design principles for content management system in multichannel content production - Jokiniemi, Emmakaisa (My University, 2019)
Newsrooms are producing content for several channels and therefore journalists’ need to operate in multiple channels in their daily work. Operating in several channels simultaneously makes content management process complex. Making this complex production effective, newsrooms’ content management tools should be given special attention in terms of usability, which is a quality attribute in information system. This thesis is an interpretive case study which examines multichannel content production in a content management system in news production context. The case in this study is a content management system called CUE and its new feature, multichannel publishing feature. The aim of the thesis is to gain better understanding about content management system’s usability by identifying both usability problems and characteristics that support a user in multichannel content production. The objective of the study is to form design principles for content management system which is used for multichannel content production. Literature review consists of literature considering multichannel news production and usability in content management systems. Data in this study was collected by utilizing two methods: First, a heuristic evaluation was conducted for multichannel publishing feature’s prototype. Content management specific heuristics were used as an evaluation framework. Second, system was evaluated in cooperative evaluation with six editorial staff representatives (n=6). Based on the data, the set of design principles for content management system in multichannel content production was formed. The main findings in this study are that clear navigation solutions, story centric workflow and ability to edit content in multiple channels simultaneously are factors in the system design, which support users to complete typical tasks in multichannel content production. However, the complexity in story reusing and editing, visibility of some UI elements and unclear terminology were seen as potential usability challenges. Considering these findings, six design principles were formed. Principles consider story centric design, supporting multiple and complex workflows, flexibility of publishing and clear indication of system status, navigation across content, story reusing and centralized content updating.
Keywords: content management system; usability; news production; fi=Tietojärjestelmätiede|en=Information Systems|; fi=Teknisen viestinnän koulutusohjelma|en=Technical Communication Programme|